Epinephrine affects motility, and increases adhesion, biofilm and virulence of Pseudomonas aeruginosa H103 - Mélyssa Cambronel (Nature Portfolio, 2019)
Abstract Microbial endocrinology has demonstrated for more than two decades, that eukaryotic substances (hormones, neurotransmitters, molecules of the immune system) can modulate the physiological behavior of bacteria. Among them, the hormones/neurotransmitters, epinephrine (Epi) and norepinephrine (NE), released in case of stress, physical effort or used in medical treatment, were shown to be able to modify biofilm formation in various bacterial species. In the present study, we have evaluated the effect of Epi on motility, adhesion, biofilm formation and virulence of Pseudomonas aeruginosa, a bacterium linked to many hospital-acquired infections, and responsible for chronic infection in immunocompromised patients including persons suffering from cystic fibrosis. The results showed that Epi increased adhesion and biofilm formation of P. aeruginosa, as well as its virulence towards the Galleria mellonella larvae in vivo model. Deciphering the sensor of this molecule in P. aeruginosa and the molecular mechanisms involved may help to find new strategies of treatment to fight against this bacterium.